TVET Research in SSA: Recommendations for Thematic Priorities - Haßler, Björn; Haseloff, Gesine (Africa Journal of Technical and Vocational Education and Training, 2022)
This paper builds on our study on research on Technical and Vocational Education and Training (TVET) in sub-Saharan Africa (SSA). The study was commissioned by the German Federal Ministry of Education and Research (Bundesministerium für Bildung und Forschung, BMBF) and was conducted in 2019. Our study undertook a systematic literature review, which evaluated over 2,000 scientific publications, classifying some 300 as relevant to the topic and examined them in greater detail. One focus area was the institutionalisation of research on TVET in sub-Saharan Africa, its actors, networks and funding. A second area focused on the topics and content addressed by researchers on TVET in SSA. Our comprehensive study allows us to derive indications for future TVET research in SSA, which form the content of the present paper. Our recommendations for future research emerge from: The research literature analysed; A series of expert interviews; and A Structured Community Review. Our key contribution is an extension of the Mulder-Roelofs Vocational Education and Training Research Framework of categories for TVET research. The framework reflects the focus and quality criteria of European/German TVET, and is an ideal starting point. Through our research, we revised and extended the framework for use in SSA. Our goal was to build on international standards on the one hand, but on the other hand to extend and apply those for use in SSA. It therefore makes it possible to respond to the latest state of research both from a European perspective (e.g., donors/organisations like BMBF), as well as to examine the broad spectrum of very different aspects of TVET research in SSA. After presenting the relevant categories of TVET research, the authors go into detail on the topics for further research. Their conclusion recommends continuous research monitoring based on a constantly updated international network of researchers and institutions with an interest in TVET research in SSA. In particular, we propose a coordinated effort for an online, international community of stakeholders and researchers involved in TVET research in sub-Saharan Africa (https://convet.org).
Keywords: Author:OpenDevEd; AuthorFirst:Haßler; Education; Internationalisation; Research; TVET; Teacher; Work Based; _bjoern_cv; _genre:LR-literature_review; _r:ImportedToMyEducationEvidence; _yl:a